Control of Type 1 and 2 Diabetes in Middle-Aged Individuals at Private Clinics in Metropolitan Lima: A Technological Solution Based on Wearables and IoT - Zapata, Diego (2024)
The control of type 1 and type 2 diabetes in individuals aged 55 to 64 seeks a non-invasive alternative for continuous monitoring of blood glucose levels. In Peru, there is poor accessibility for data collection within the monitoring of this disease due to economic resources and lack of technical support. Therefore, a technological solution is proposed that integrates the use of IoT and wearable technologies, such as smartwatches, to collect and monitor real-time heart rate data, integrating the Google Fit API as our data source. This solution aims to strengthen and improve the quality of the managed data in order to facilitate the treatment of diabetic patients. The solution was validated with 20 users, of which 15 were diabetic patients and the remaining 5 were endocrinologists. For this process, they registered in the application, used it for a certain period of time to collect sufficient data, and filled out a satisfaction survey. The results obtained show that a satisfaction rate of over 75% was achieved, indicating that this technological solution allows for more accurate and continuous monitoring, facilitating self-management for patients and providing real-time information to physicians for control purposes.